Strategi Pengelolaan dan Pengembangan Objek Wisata Gunung Pa’baladoan pada Lembang Belau Kecamatan Masanda Kabupaten Tana Toraja - Alwin Paemba; Helba Rundupadang; Mince Batara (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to analyze and formulate a management and development strategy for Mount Pa'baladoan tourism in Tana Toraja Regency using SWOT analysis. Qualitative research method with data collection through interviews, observation and documentation studies. The results of the SWOT analysis show that Mount Pa'baladoan has strengths in the form of natural beauty, cultural richness, accessibility and local wisdom. However, there are weaknesses such as management that is not optimal, limited human resource capacity, and promotion that is less effective. The opportunities that exist are tourism growth, government support, and ecotourism-oriented community lifestyles. Meanwhile, the threats are competition from other destinations, natural disasters, as well as the impact of globalization and cultural westernization. Based on the SWOT analysis, the Mount Pa'baladoan tourism development strategy includes SO, WO, ST and WT strategies. The implementation of these strategies is expected to increase the competitiveness and sustainability of Mount Pa'baladoan tourism development in Tana Toraja Regency